2012
DOI: 10.1002/jso.23215
|View full text |Cite
|
Sign up to set email alerts
|

Patient reasoning in palliative surgical oncology

Abstract: The most common reasons for treatment selection in palliative surgical consultation include symptom relief or improvement in quality of life and the doctor's recommendation with few patients listing concerns over surgical morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Patients were willing to prioritize survival over intact sexual function in prostate cancer for instance . When patients with advanced cancer reached the end of their lives and had to endure pain and discomfort, 47% of patients chose to have palliative surgery to maintain or enhance their current health status and independence …”
Section: Resultsmentioning
confidence: 99%
“…Patients were willing to prioritize survival over intact sexual function in prostate cancer for instance . When patients with advanced cancer reached the end of their lives and had to endure pain and discomfort, 47% of patients chose to have palliative surgery to maintain or enhance their current health status and independence …”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is that symptoms may not have been the primary outcome of importance to some patients. Previous research has demonstrated that less than half of patients who receive palliative surgical consultation choose their management strategy based on a desire for improved quality of life or symptom improvement; rather, they choose their treatment based on their physician's recommendation or a desire to live longer . Therefore, in addition to the FACT‐G and/or an open‐ended questionnaire, a measure of treatment satisfaction that asks patients whether the surgical intervention was “worth it” or whether they would choose the same management strategy again might be a helpful outcome measure in palliative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative surgical procedures are intended to reduce suffering or support quality of life rather than prolong life or cure disease. 34,35,47 Prior studies have described the considerable risks of postoperative complications and mortality after palliative surgery, but few have measured the impact of palliative surgery on restoration of function and quality of life, or conversely, the occurrence of adverse outcomes that further threaten quality of life, function, and ability to achieve a good death. 26,48 Absence of a uniform system for designating and classifying procedures performed with palliative intent presents a barrier to studying outcomes of palliative surgery.…”
Section: Priority Area 1: Measuring Outcomes That Matter To Patientsmentioning
confidence: 99%